Kilovoltage beam Monte Carlo dose calculations in submillimeter voxels for small animal radiotherapy - Bazalova, Magdalena (American Association of Physicists in Medicine, 2009)
Purpose: Small animal conformal radiotherapy (RT) is essential for preclinical cancer research studies and therefore various microRT systems have been recently designed. The aim of this paper is to efficiently calculate the dose delivered using our microRT system based on a microCT scanner with the Monte Carlo (MC) method and to compare the MC calculations to film measurements. Methods: Doses from 2–30 mm diameter 120 kVp photon beams deposited in a solid water phantom with 0.2×0.2×0.2 mm(3) voxels are calculated using the latest versions of the EGSnrc codes BEAMNRC and DOSXYZNRC. Two dose calculation approaches are studied: a two-step approach using phase-space files and direct dose calculation with BEAMNRC simulation sources. Due to the small beam size and submillimeter voxel size resulting in long calculation times, variance reduction techniques are studied. The optimum bremsstrahlung splitting number (NBRSPL in BEAMNRC) and the optimum DOSXYZNRC photon splitting (N(split)) number are examined for both calculation approaches and various beam sizes. The dose calculation efficiencies and the required number of histories to achieve 1% statistical uncertainty—with no particle recycling—are evaluated for 2–30 mm beams. As a final step, film dose measurements are compared to MC calculated dose distributions. Results: The optimum NBRSPL is approximately 1×10(6) for both dose calculation approaches. For the dose calculations with phase-space files, N(split) varies only slightly for 2–30 mm beams and is established to be 300. N(split) for the DOSXYZNRC calculation with the BEAMNRC source ranges from 300 for the 30 mm beam to 4000 for the 2 mm beam. The calculation time significantly increases for small beam sizes when the BEAMNRC simulation source is used compared to the simulations with phase-space files. For the 2 and 30 mm beams, the dose calculations with phase-space files are more efficient than the dose calculations with BEAMNRC sources by factors of 54 and 1.6, respectively. The dose calculation efficiencies converge for beams with diameters larger than 30 mm. Conclusions: A very good agreement of MC calculated dose distributions to film measurements is found. The mean difference of percentage depth dose curves between calculated and measured data for 2, 5, 10, and 20 mm beams is 1.8%.